THE INFLUENCE OF ISLAMIC RELIGIOSITY ON STUDENTS' FINANCIAL WELL-BEING THROUGH FINANCIAL BEHAVIOR: MODERATING ROLE OF FINANCIAL LITERACY - Suriyanti, Linda Hetri; Ardiansyah, Fadly; Fitriana, Nur (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The low level of financial well-being among university students, particularly in Pekanbaru, has become a severe concern as the number of individuals living in poverty rises and risky financial habits such as online gambling and loans become more common. This study investigates the role of Islamic religiosity in improving students' financial well-being by examining financial behavior as a mediator and financial literacy as a moderator. A survey of 124 students from four universities in Pekanbaru was conducted, and the data were analyzed using PROCESS Macro Model 8 in SPSS 25. The findings reveal that Islamic religiosity directly and indirectly influences financial well-being through financial behavior. Moreover, financial literacy strengthens the relationship between Islamic religiosity and financial behavior, but not the direct link between religiosity and financial well-being. Beyond the statistical results, this study contributes theoretically by integrating moderated mediation analysis into the context of student financial well-being, an approach rarely applied in prior studies. The results highlight the need to promote religious values and financial literacy in higher education policies and student development programs as effective strategies to foster healthier financial behavior and improve financial well-being.